Bis 3,3-dimethyl-2-(2-oxoethylidene)indolinyl-kappa N-2,O palladium(II) - Khaledi, H.; Ali, Hapipah Mohd; Olmstead, M.M. (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, [Pd(C12H12NO)(2)], consists of three crystallographically independent half-molecules. Each Pd-II atom lies on a center of inversion and is four-coordinated by two monoanionic forms of the aminoacrylaldehyde in a square-planar geometry. In the crystal, adjacent molecules are connected through C-H center dot center dot center dot pi and C-H center dot center dot center dot O interactions into a three-dimensional polymeric structure.